2017
DOI: 10.1093/geronb/gbx020
|View full text |Cite
|
Sign up to set email alerts
|

Association of Anxiety Symptom Clusters with Sleep Quality and Daytime Sleepiness

Abstract: These findings indicate that anxiety symptom clusters are differentially associated with specific sleep-related disturbances, underscoring the complex relationship of late-life anxiety to sleep. Results suggest that personalized treatments, such as targeted sleep interventions, may improve specific anxiety-symptom domains, or vice versa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 36 publications
6
27
0
Order By: Relevance
“…This study presents the association between poor sleep quality and anxiety symptoms, which is consistent with a previous study that poor sleep quality were strongly associated with anxiety symptoms among women [32]. Previous studies on patients with coronary artery bypass graft patients identi ed that a better quality of sleep was related to lower anxiety levels [8,33].…”
Section: Discussionsupporting
confidence: 91%
“…This study presents the association between poor sleep quality and anxiety symptoms, which is consistent with a previous study that poor sleep quality were strongly associated with anxiety symptoms among women [32]. Previous studies on patients with coronary artery bypass graft patients identi ed that a better quality of sleep was related to lower anxiety levels [8,33].…”
Section: Discussionsupporting
confidence: 91%
“…We think there maybe correlation between physical health and mental health that the previous similar studies shown the same viewpoint [60].We also found nurses with sleep disorder or anxiety symptoms have lower quality of life, no matter PCS or MCS. The results may indicate that sleep disorder and anxiety symptom could respect poor quality of life.…”
Section: Prevalence and Influencing Factors Of Anxiety Symptoms Amongsupporting
confidence: 67%
“…Syntheses of longitudinal studies suggested sleep quality were bidirectionally related to anxiety [30]. There were large data investigating the effect of sleep quality on the anxiety symptom in other populations such as shiftworkers, re ghters, paramedics, pregnant women, older adults, poor sleep quality had higher odds of anxiety symptoms, greater anxiety were associate with poorer sleep quality [31][32][33][34][35]. Similarly, anxiety affects sleep quality because anxious people nd it hard to fall asleep and wake up frequently [30].…”
Section: Discussionmentioning
confidence: 99%